Spectrophotometric Determination of Nirite By The Diazotization Coupling With Aniline and 4,6 Dihydroxy-2 Mercaptopyrimidine - Mohammed, H. J.; Hassan, D.S.; Hmood, A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A direct spectrophotometric method has been developed for the determination of nitrite in aqueous solution. The method is based on the reaction of the nitritw ion with an acidified anline solution from diazonium cation , which is subsequently coupled Â·with 4,6 - dihydroxy- 2- mercapto pyrimidine to from yellow colored and water - soluble intense azo dye with maximum absorption at 416nm . A graph of absorbance versus concentration shows that Bee’s Laws obeyed over the concentration rang of 20 -100 ug of nitrite in final 3 volume of ml(i.e., 2-10 ppm) with a molar absorpitivity of (3.5x 10 0.12j.lg.cmÂ· ) L.mole" 1 .cm"1) >a Sandall sensitivity of ( 2 , a relative error of (-0.05%) (-0.65%) and a relaLive standard deviation (0,&6-1.0%) depending on the concentration.